Determinants of Dividend Policy in the Indian Corporate Sector : A Study of Companies Listed on Nifty 50, NSE - Venkataramanaiah, M.; Madhavi Latha, Ch.; Siva Nageswara Rao, K. (Indian Journal of Finance, 2018)
The present study investigated determinants of dividend policy of Nifty 50 of National Stock Exchange of India Limited (NSE). The paper examined the effects of four basic variables on the dividend policy. These factors included economic performance of organizations, liquidity, leverage, and size of the firm. Regression analysis was employed to study the selected determinants that affected the dividend payout policy of the firms listed on the NSE. A positive and significant relationship was found in between organization's economic performance (ROE) and dividend payout policy, while a significant negative relationship was found between size and dividend policy. In contrast, a negative relationship and no significance was found in between liquidity and dividend payout policy. The same tendency was found in between leverage and dividend policy of the listed sample companies of Nifty 50.